2021
DOI: 10.1021/acsomega.1c03481
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Carbon Dots as Biosensor, Green Reductant, and Biomarker

Abstract: Carbon dots, the celebrated green material among the nanocarbon family, are blessed with several interesting features like biocompatibility, solubility, tunable luminescence, and so forth. Herein, carbon dots derived from Mint leaf extract (M-CDs) via a green method are exploited for versatile applications as a biosensor, reductant, and biomarker. M-CDs are applied for fluorimetric sensing of biologically relevant folic acid through quenching response originating from the inner filter effect, with a limit of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…The prepared system could act as an effective and selective sensor of folic acid realized through fluorescence quenching, with a limit of detection of 4.5 μM. The specific quenching [27] in the luminescence of CO‐CDs in presence of folic acid is credited to the inner filter effect [4b,28,4b,25,28b,29] . The practical use of the sensor has been confirmed by real sample analysis, by quantifying folic acid present in commercially available Folate tablets [30] .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The prepared system could act as an effective and selective sensor of folic acid realized through fluorescence quenching, with a limit of detection of 4.5 μM. The specific quenching [27] in the luminescence of CO‐CDs in presence of folic acid is credited to the inner filter effect [4b,28,4b,25,28b,29] . The practical use of the sensor has been confirmed by real sample analysis, by quantifying folic acid present in commercially available Folate tablets [30] .…”
Section: Introductionmentioning
confidence: 81%
“…Carbon dots are spheroid zero‐dimensional nanoparticles with a size of less than 10 nm, marked with a carbon core and associated functional groups. The above‐mentioned outstanding properties of C‐ dots have made it a comparitively eco‐friendly candidate for potential applications in nanotechnology [3] including bio‐imaging, [4] sensing [3,4b,,5e] photocatalysis, [6] and light‐emitting devices., [,7a,c–e,8] The exceptional chemical and photochemical stability of CDs accompanied by their biocompatibility enhances the potential of carbon dots as a promising attractive material for substantial application in bioimaging and selective detection of inorganic molecules., [,9c9b] This in turn signifies carbon dots as an excellent competitor for conventional toxic heavy metal‐based quantum dots [10] . Up to now, a variety of methods are employed for the development of CDs, which can be roughly sorted into two; as top‐down and bottom‐up [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews have been reported on nonmetal-doped CDs and their applications [ 10 , 27 , 41 , 48 , 49 , 50 , 53 ] However, we found no review on the advancement of metal/nonmetal-doped/hybrid CDs, describing their physical or chemical properties and biomedical applications. The current review describes the recent progress in metal/nonmetal-doped/hybrid CD-based technology, considering their bottom-up synthetic procedures, the effect of doping or conjugation on the structure and the physical properties of the nanocomposites and their biomedical applications, which includes bioimaging, antimicrobial activity, drug delivery, cancer therapy, neuron tissue engineering and bio-sensor applications.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, the presence of metal atoms in CDs results in an increase in their electrical conductivity as well as electron transfer and electron-acceptance capabilities, which facilitates electron transfer and increases their photocatalytic activity over pristine CDs [ 48 , 49 ]. Furthermore, CDs can act as an excellent reducing agent and reduce incorporated metal ions thus forming metal-doped CDs [ 50 ]. Conjugation of metal oxide nanomaterials with CDs or polymers improves their light-induced reactive oxygen species (ROS) production rate [ 5 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are suitable for effective high-throughput detection methods, and in contrast, FIA has higher sensitivity. Carbon dots (CDs) are a class of zero-dimensional fluorescent nanomaterials based on carbon, and have emerged in recent years ( Raveendran and Kizhakayil, 2021 ). Compared with traditional fluorescent nanomaterials (e.g., quantum dots), it can synthesize CDs in a simple way, and have the advantage of low cost, good photostability and low toxicity.…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%